Preparation method of high-purity nanometer titanium dioxide
Patent Information
- Application Number
- CN202512012491.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-12-29
AI Technical Summary
[0009]传统采用四氯化钛原料直接汽化进行高温水解,然后经过系列后处理得到气相法纳米二氧化钛的方法中,在控制产品的氯含量、金属杂质含量及磁性异物含量方面存在困难,难以满足催化剂及锂离子电池材料应用要求
[0038]In this invention, when preparing nano-titanium dioxide using the gas-phase method, the inventors discovered that by filtering the reaction raw material TiCl4 and the reaction gas before it enters the reactor, and heating and filtering the deacidification auxiliary gas before it enters the deacidification device, and by demagnetizing the deacidified nano-titanium dioxide product, combined with controlling the specific heating temperature of the input deacidification auxiliary gas, it is possible to obtain nano-titanium dioxide products with an anatase crystal ratio of over 80%, while effectively controlling the content of chlorine, iron, sodium, calcium, copper, zinc, cadmium, chromium, lead, and magnetic foreign matter in the nano-titanium dioxide product, thus obtaining high-purity nano-titanium dioxide with a high anatase crystal ratio.
Smart Images

Figure CN121449103B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic chemistry technology, specifically relating to a method for preparing high-purity nano-titanium dioxide. Background Technology
[0002] Nano-titanium dioxide is a polycrystalline powder, mainly existing in three crystalline forms in nature: anatase, rutile, and brookite. Among these, the brookite and anatase structures are not stable crystal forms and can both transform into the rutile form at high temperatures. The transformation temperature from anatase to rutile titanium dioxide is generally around 550℃, but as the size of the titanium dioxide particles decreases, their transformation temperature decreases. Nano-sized titanium dioxide begins to undergo crystal transformation at as low as 400℃.
[0003] Common gas-phase methods for preparing nano-titanium dioxide include high-temperature oxidation and high-temperature hydrolysis. High-temperature oxidation involves the reaction of silicon tetrachloride with oxygen to obtain nano-titanium dioxide; while high-temperature hydrolysis involves the high-temperature hydrolysis of titanium tetrachloride with hydrogen and oxygen to obtain nano-titanium dioxide. Their reaction mechanisms are as follows.
[0004] TiCl4 + O2 = TiO2 + Cl2;
[0005] TiCl4 + H2 + O2 = TiO2 + HCl.
[0006] High-temperature oxidation produces chlorine gas as a byproduct, and the post-treatment process is complex and poses safety hazards; high-temperature hydrolysis is relatively easy to treat the tail gas, so high-temperature hydrolysis is the more common method.
[0007] Nano-titanium dioxide prepared by the gas-phase method has wide applications in the field of catalysts due to its high purity, small particle size, large specific surface area, and mixed anatase and rutile crystal structure, serving as a catalyst material or catalyst support. In the modification of lithium-ion battery cathode materials, nano-titanium dioxide can also act as a protective layer, reducing electrolyte corrosion of the cathode. Furthermore, it can promote the formation of a uniform and dense CEI film on the surface, reducing electrolyte decomposition and gas generation. Nano-titanium dioxide can also form bonds with the cathode material, inhibit the dissolution of transition metal ions during charge and discharge, and act as a rigid support, reducing stress concentration in the cathode particles. In addition, nano-titanium dioxide can improve battery capacity and enhance the high-temperature stability of batteries.
[0008] However, in the field of catalysts, the requirements for the crystal structure of nano-titanium dioxide and the impurities in the product are extremely high, especially the content of metallic impurities and chlorides, which have a significant impact on the catalytic performance of the material. Typically, the proportion of anatase crystals is required to be greater than 80%, and the chloride content is required to be less than 3000 ppm. In lithium-ion battery materials, the requirements for magnetic foreign matter and metallic impurities such as iron, zinc, manganese, copper, sodium, and calcium are even more stringent. Typically, magnetic foreign matter content is required to be less than 100 ppb, iron content less than 30 ppm, copper, zinc, and chromium content less than 10 ppm, sodium and calcium content less than 200 ppm, lead content less than 5 ppm, and metal particles of 25-100 micrometers less than 100 per kg.
[0009] The traditional method of obtaining gas-phase nano-titanium dioxide by directly vaporizing titanium tetrachloride raw material for high-temperature hydrolysis and then performing a series of post-processing steps has difficulties in controlling the chlorine content, metal impurity content and magnetic foreign matter content of the product, making it difficult to meet the application requirements of catalysts and lithium-ion battery materials. Summary of the Invention
[0010] The purpose of this invention is to provide a method for preparing high-purity nano-titanium dioxide, which can effectively reduce the content of chloride and metal impurities in the prepared nano-titanium dioxide.
[0011] The following technical solutions are used to achieve the above objectives.
[0012] The first aspect of this invention provides a method for preparing high-purity nano-titanium dioxide, comprising the following steps:
[0013] The reactant TiCl4 and the reactant gas were filtered separately and then mixed in the reactor.
[0014] The resulting mixture is ignited and then fed into a reactor for combustion to obtain reaction products;
[0015] The resulting reaction product is fed into a deacidification device, and a deacidification auxiliary gas, which has been successively heated and filtered, is also fed into the deacidification device. The deacidification auxiliary gas and the reaction product are mutually counteracted in the deacidification device to deacidify the product and obtain nano-titanium dioxide. The temperature of the deacidification auxiliary gas is 450℃~600℃.
[0016] The obtained nano-titanium dioxide is demagnetized by passing it through a demagnetizer, thus obtaining the high-purity nano-titanium dioxide.
[0017] In some embodiments, the TiCl4 in the reaction raw materials is liquid, and the TiCl4 liquid is filtered through a first filter and then vaporized and introduced into the reactor; the first filter is provided with a first filter element, and the TiCl4 liquid enters from the bottom of the first filter, flows through the first filter element, and then flows out from the top of the first filter.
[0018] In some embodiments, the first filter element is porous polytetrafluoroethylene with a pore size of 0.005 μm to 0.1 μm, preferably 0.008 μm to 0.05 μm;
[0019] And / or, the first filter element is provided in multiple parts, each of the first filter elements is tightly fitted together, and the outer wall of the outermost first filter element is in close contact with the inner wall of the first filter.
[0020] In some embodiments, the reaction gas includes hydrogen and combustion-supporting gas; the hydrogen and combustion-supporting gas are filtered through a second filter before being introduced into the reactor;
[0021] The second filter includes multiple gas filters connected in series to form a multi-stage filtration structure; each gas filter is provided with a second filter element, the pore size of the second filter element is 0.005μm~1μm, and the pore size of the second filter element in the gas filter from the first stage to the last stage decreases sequentially.
[0022] In some embodiments, the second filter includes three gas filters connected in series; the second filter element in the first-stage gas filter has a pore size of 0.3 μm to 0.7 μm, the second filter element in the second-stage gas filter has a pore size of 0.08 μm to 0.2 μm, and the second filter element in the third-stage gas filter has a pore size of 0.008 μm to 0.05 μm.
[0023] In some embodiments, the deacidification auxiliary gas is air or nitrogen;
[0024] And / or, the deacidification auxiliary gas is mixed with vaporized pure water, heated by an electromagnetic heater, filtered through another second filter, and then enters the deacidification device from the bottom to counteract the reaction products input from the top of the deacidification device for deacidification.
[0025] In some embodiments, the demagnetizer includes a delivery tube, a contact tube, and a magnetic rod;
[0026] The conveying pipe has a conveying channel inside, and the conveying pipe is connected to the deacidification device;
[0027] The contact tube is inserted through the body of the conveying tube and is arranged along the intersecting direction of the conveying channel; the contact tube is a magnetically penetrable structure; at least one end of the contact tube is an open end, and the magnetic rod is movably disposed inside the contact tube and can be pulled away from the contact tube along the open end.
[0028] In some embodiments, the open end of the contact tube is provided with a movably closing sealing cap, and the sealing cap is provided with an air inlet that communicates with the internal space of the contact tube. The contact tube located inside the conveying tube body is provided with a blow hole. There is a cavity between the outer wall of the magnetic rod and the inner wall of the contact tube. The air inlet, the cavity and the blow hole are sequentially connected to form a blow channel.
[0029] In some embodiments, the magnetic rod includes a magnetic rod body and a protective sleeve, the protective sleeve being fitted onto the magnetic rod body, and the protective sleeve having a magnetically permeable structure.
[0030] And / or, the axial line of the blow hole is inclined relative to the radial line of the contact tube, and the blow hole extends along the circumferential direction of the contact tube to form an arc-shaped inclined hole structure in the tube body of the contact tube.
[0031] And / or, the conveying pipe body has an input end and an output end communicating with the conveying channel, and both the input end and the output end are provided with flange connectors;
[0032] And / or, multiple contact tubes and magnetic rods are provided, with each contact tube and magnetic rod corresponding to the other, and the distance between two adjacent contact tubes is 10mm to 50mm.
[0033] In some embodiments, the deacidification device includes multiple deacidification furnaces connected in series to form a multi-stage deacidification structure;
[0034] And / or, after the resulting mixture is ignited and enters the reactor for combustion reaction, and before the resulting reaction product is input into the deacidification unit, the following steps are also included:
[0035] The obtained reaction product is passed into an aggregator to aggregate the solid product to obtain an aggregate, and the obtained aggregate is passed into a cyclone separator to separate the solid reaction product.
[0036] And / or, the temperature inside the reactor is 280℃~400℃;
[0037] And / or, the temperature of the deacidification auxiliary gas is 500℃~580℃, preferably 540℃~560℃.
[0038] In this invention, when preparing nano-titanium dioxide using the gas-phase method, the inventors discovered that by filtering the reaction raw material TiCl4 and the reaction gas before it enters the reactor, and heating and filtering the deacidification auxiliary gas before it enters the deacidification device, and by demagnetizing the deacidified nano-titanium dioxide product, combined with controlling the specific heating temperature of the input deacidification auxiliary gas, it is possible to obtain nano-titanium dioxide products with an anatase crystal ratio of over 80%, while effectively controlling the content of chlorine, iron, sodium, calcium, copper, zinc, cadmium, chromium, lead, and magnetic foreign matter in the nano-titanium dioxide product, thus obtaining high-purity nano-titanium dioxide with a high anatase crystal ratio. Attached Figure Description
[0039] Figure 1 This is a flowchart illustrating the preparation process of high-purity nano-titanium dioxide according to an embodiment of the present invention.
[0040] Figure 2 This is a schematic diagram of the structure of the second filter according to an embodiment of the present invention.
[0041] Figure 3 This is a longitudinal cross-sectional structural diagram of the gas filter according to an embodiment of the present invention.
[0042] Figure 4 This is a side view of the demagnetizer according to an embodiment of the present invention.
[0043] Figure 5 This is a schematic diagram of the assembly structure of the contact tube and magnetic rod according to an embodiment of the present invention.
[0044] Figure 6 This is a schematic diagram of the arrangement of the blow holes on the contact tube according to an embodiment of the present invention.
[0045] Figure 7 This is a detailed structural diagram of the blow hole at one angle according to an embodiment of the present invention.
[0046] Figure 8 This is a detailed structural diagram of the blow hole from another angle according to an embodiment of the present invention.
[0047] Figure 9 This is a schematic diagram of the structure of the first filter according to an embodiment of the present invention.
[0048] Explanation of reference numerals in the attached figures:
[0049] 1. Demagnetizer; 11. Conveying pipe; 12. Contact pipe; 121. Sealing cover; 122. Air inlet; 123. Blowing hole; 13. Magnetic rod; 14. Flange connector; 2. First filter; 3. Second filter; 31. Gas filter; 311. First cylinder; 312. Second cylinder; 313. Gas inlet; 314. Gas outlet; 315. Second filter element; 4. Reactor; 5. Furnace; 6. Collector; 7. Cyclone separator; 8. Deacidification device; 81. Deacidification furnace; 9. Electromagnetic heater. Detailed Implementation
[0050] To facilitate understanding of the present invention, a more complete description will be provided below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.
[0051] Unless otherwise specified, experimental methods in the following examples are generally performed under standard conditions or as recommended by the manufacturer. All commonly used chemical reagents used in the examples are commercially available products.
[0052] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. The term "and / or" as used in this invention includes any and all combinations of one or more of the associated listed items.
[0053] This invention provides a method for preparing high-purity nano-titanium dioxide, such as... Figures 1 to 9 As shown, it includes the following steps:
[0054] The reactant TiCl4 and the reactant gas were filtered separately and then mixed in reactor 4;
[0055] The resulting mixture is ignited and then enters reactor 5 for combustion reaction to obtain reaction products;
[0056] The resulting reaction product is fed into the deacidification device 8, and the deacidification auxiliary gas, which has been heated and filtered in sequence, is also fed into the deacidification device 8. The deacidification auxiliary gas and the reaction product are mutually counteracted in the deacidification device 8 to deacidify the product and obtain nano-titanium dioxide.
[0057] The obtained nano-titanium dioxide is passed into demagnetizer 1 for demagnetization, thus obtaining the high-purity nano-titanium dioxide.
[0058] The temperature of the deacidification auxiliary gas is 450℃~600℃, preferably 500℃~580℃, and more preferably 540℃~560℃.
[0059] In this invention, when preparing nano-titanium dioxide using the gas-phase method, the inventors discovered that by filtering the reaction raw material TiCl4 and the reaction gas before it enters reactor 4, and heating and filtering the deacidification auxiliary gas before it enters deacidification device 8, and by demagnetizing the deacidified nano-titanium dioxide product, combined with controlling the specific heating temperature of the input deacidification auxiliary gas, it is possible to obtain nano-titanium dioxide products with an anatase crystal ratio of over 80%, while effectively controlling the content of chlorine, iron, sodium, calcium, copper, zinc, cadmium, chromium, lead, and magnetic foreign matter in the nano-titanium dioxide product, thus obtaining high-purity nano-titanium dioxide with a high anatase crystal ratio.
[0060] The nanopowder preparation apparatus used in the above-mentioned method for preparing high-purity nano-titanium dioxide of the present invention is as follows: Figures 1 to 8 As shown, the device includes a first filter 2, a second filter 3, a reactor 4, a reaction furnace 5, an aggregator 6, a cyclone separator 7, a deacidification device 8, and a demagnetizer 1. The first filter 2 and the two second filters 3 are respectively connected to the inlet of the reactor 4. The outlet of the reactor 4, the reaction furnace 5, the aggregator 6, the cyclone separator 7, the deacidification device 8, and the demagnetizer 1 are connected in sequence. The deacidification device 8 is also connected to a deacidification auxiliary gas channel, which is equipped with an electromagnetic heater 9 and one of the second filters 3. The deacidification auxiliary gas is fed into the deacidification device 8 after passing through the electromagnetic heater 9 and the second filter 3 in sequence.
[0061] In some implementations, such as Figure 9 As shown, the TiCl4 in the reaction raw material is liquid. The TiCl4 liquid is filtered through the first filter 2 and then vaporized before being introduced into the reactor 4. The first filter 2 is equipped with a first filter element. The TiCl4 liquid enters from the bottom of the first filter 2, flows through the first filter element, and then flows out from the top of the first filter 2. It is understandable that using TiCl4 liquid as a reaction raw material is problematic because TiCl4 liquid usually contains insoluble solid particles such as metal oxide particles, carbon particles, soluble metal chlorides such as FeCl3 and AlCl3, and hydrolyzed colloids introduced during preparation or storage. If the TiCl4 liquid is vaporized and then filtered, experiments have shown that some impurities may be carried away by the steam or undergo thermal decomposition, increasing the difficulty of subsequent separation. Therefore, in this embodiment, a specific step of precision filtration and revaporization in the TiCl4 liquid state is adopted, which can efficiently intercept solid and colloidal impurities, thereby effectively removing impurities from the vaporized TiCl4 introduced into the reactor 4, obtaining high-purity TiCl4 for subsequent reactions in the reactor 4.
[0062] In some embodiments, the first filter element is porous polytetrafluoroethylene (PTFE) with a pore size of 0.005 μm to 0.1 μm, preferably 0.008 μm to 0.05 μm. Understandably, porous PTFE within this pore size range can effectively intercept nanoscale solid particles and hydrolyzed colloidal impurities in TiCl4 liquid, thereby ensuring high-purity TiCl4 and guaranteeing filtration throughput while improving filtration efficiency.
[0063] In some embodiments, multiple first filter elements are provided, with each first filter element closely fitted together, and the outer wall of the outermost first filter element is in close contact with the inner wall of the first filter 2, which can effectively increase the filtration area and ensure that TiCl4 liquid can only flow out from the first filter element, thereby improving the filtration effect.
[0064] In some embodiments, the reactant gas includes hydrogen and an oxidizing agent; the hydrogen and the oxidizing agent are filtered through a second filter 3 before being introduced into the reactor 4; wherein, when vaporized titanium tetrachloride is introduced into the reactor 4 at a flow rate of 15 kg / h, hydrogen enters the reactor 4 at a flow rate of 0.1 kg / h to 0.5 kg / h, preferably 0.4 kg / h to 0.5 kg / h, and the oxidizing agent enters the reactor 4 at a flow rate of 35 kg / h to 50 kg / h, preferably 45 kg / h to 50 kg / h. Specifically, the oxidizing agent can be oxygen or air. The second filter 3 includes a plurality of gas filters 31 connected in series to form a multi-stage filtration system; each gas filter 31 is provided with a second filter element 315, the pore size of the second filter element 315 is 0.005 μm to 1 μm, and the pore size of the second filter element 315 in the gas filter 31 decreases sequentially from the first stage to the last stage. It should be noted that both hydrogen and combustion-supporting gas are filtered through an independent second filter 3 before entering reactor 4. Understandably, hydrogen and combustion-supporting gas also contain particulate impurities, which, once introduced into reactor 4, will affect product quality. In this embodiment, a gradient precision filtration system is formed by multiple gas filters 31 connected in series. This system can efficiently intercept particulate matter of different sizes in the gas, such as dust, moisture aerosols, and metal particles, thereby effectively filtering out impurities from the gas.
[0065] In some implementations, such as Figure 2 and Figure 3As shown, the second filter 3 includes three gas filters 31 connected in series. The second filter element 315 in the first-stage gas filter 31 has a pore size of 0.3μm~0.7μm, the second filter element 315 in the second-stage gas filter 31 has a pore size of 0.08μm~0.2μm, and the second filter element 315 in the third-stage gas filter 31 has a pore size of 0.008μm~0.05μm. Understandably, by passing gas through these progressively smaller pore sizes of the second filter element 315, filtration resistance can be reduced and filtration efficiency improved.
[0066] In some implementations, such as Figure 3 As shown, the gas filter 31 includes a first cylinder 311 and a second cylinder 312. The first cylinder 311 is sleeved on the second cylinder 312, and a gas flow channel is formed between the first cylinder 311 and the second cylinder 312. The top of the second cylinder 312 communicates with the gas flow channel. The second filter element 315 is provided inside the second cylinder 312. The first cylinder 311 is provided with a gas inlet 313 communicating with the gas flow channel. The bottom of the second cylinder 312 is provided with a gas outlet 314. The gas outlet 314 of the previous stage gas filter 31 communicates with the gas inlet 313 of the next stage gas filter 31.
[0067] In some embodiments, the deacidification auxiliary gas can be at least one of dry air and nitrogen, or contain a small amount of pure water vapor. Specifically, in this embodiment, it is a mixture of air and pure water vapor, wherein the air flow rate is 40 kg / h to 60 kg / h, preferably 48 kg / h to 52 kg / h, and the water vapor flow rate is 3 kg / h to 10 kg / h, preferably 4 kg / h to 6 kg / h. Understandably, the dechlorination treatment of the nano-titanium dioxide powder is carried out within the deacidification device 8 by using a hot deacidification auxiliary gas and pure water vapor to counter-current with the nano-titanium dioxide powder, thereby using the deacidification auxiliary gas to remove the hydrogen chloride adsorbed on the powder surface.
[0068] In some implementations, such as Figure 1As shown, the deacidification auxiliary gas is mixed with vaporized pure water, heated by an electromagnetic heater 9, and then filtered through another second filter 3 before entering the deacidification device 8 from the bottom. This gas then counteracts the reaction products input from the top of the device to achieve deacidification. It can be understood that using deacidification auxiliary gas for heating of nano-titanium dioxide powder, compared to directly heating the deacidification device 8 externally (e.g., heating with heating elements inside the device), effectively avoids the problem of localized overheating causing sintering and resulting in large particles, and also effectively avoids the risk of other impurities introduced during gas-fired deacidification. The electromagnetic heater 9 includes a coiled gas pipe with an electromagnetic coil wound around its outer wall. The deacidification auxiliary gas is introduced into this gas pipe, and the gas pipe is heated electromagnetically to heat the deacidification auxiliary gas. Using the electromagnetic heater 9 to directly heat the deacidification auxiliary gas offers advantages such as fast heating speed, high heating efficiency, and low energy consumption. The subsequent filtration after heating effectively ensures that the gas entering the deacidification device 8 is free of impurities, thus effectively preventing any impact on product purity.
[0069] In some implementations, such as Figure 1 As shown, the deacidification device 8 includes multiple deacidification furnaces 81 connected in series to form a multi-stage deacidification structure. Each deacidification furnace 81 is a fluidized bed structure, with an enlarged section at the upper end to facilitate gas-solid separation and a straight cylindrical section at the lower end connected to the enlarged section to facilitate gas-solid contact and fluidization. Nano-titanium dioxide powder enters the deacidification furnace 81 from the bottom of the enlarged section, flowing downwards, while deacidification auxiliary gas is introduced from the bottom of the deacidification furnace 81, flowing upwards. Under the action of the deacidification auxiliary gas, the nano-titanium dioxide powder forms a fully fluidized state within the deacidification furnace 81, achieving gas-solid separation. Specifically, four deacidification furnaces 81 are provided, forming a four-stage deacidification structure. The powder exits from the lower end of the previous stage deacidification furnace 81 and is fed into the next stage deacidification furnace 81, undergoing four stages of deacidification treatment sequentially, effectively removing hydrogen chloride gas from the nano-titanium dioxide powder. In addition, the furnace body of the deacidification furnace 81 is equipped with heat tracing plates and an insulation layer outside the heat tracing plates to prevent heat loss.
[0070] In some implementations, such as Figure 1 As shown, after the obtained mixture is ignited and enters the reactor 5 for combustion reaction, and before the obtained reaction product is input into the deacidification device 8, the following steps are also included:
[0071] The resulting reaction product is passed into an aggregator 6 to aggregate the solid phase product, obtaining an aggregate. The resulting aggregate is then passed into a cyclone separator 7 to separate the solid phase of the reaction product. Understandably, after the mixture is ignited, it enters the reactor 5 for a combustion reaction, where the mixture undergoes a high-temperature hydrolysis reaction to generate nano-titanium dioxide particles. The temperature inside the reaction chamber is adjusted to 280-400°C, preferably 350-380°C, by controlling the ratio of the reaction gas and titanium tetrachloride gas, ensuring that the proportion of anatase crystals in the generated nano-titanium dioxide is greater than 80%. The reaction product is a gas-solid mixture composed of nano-titanium dioxide, hydrogen chloride, and excess air. The generated nano-titanium dioxide particles are very small (<100nm) and have a very low concentration, making them difficult to collect. Therefore, the gas-solid mixture needs to pass through the aggregator 6 to allow the particles to collide and form aggregates with a particle size of 0.2-5 micrometers for easier collection. The material exiting from the collector 6 enters the cyclone separator 7 for gas-solid separation. Under the action of centrifugal force, the powder is separated, while the gas enters the bag filter from the top. The tail gas separated by the bag filter is treated and discharged in compliance with standards. The powder separated by the bag filter and the powder separated by the cyclone separator 7 enter the deacidification device 8 from the bottom for deacidification treatment.
[0072] After deacidification, the nano-titanium dioxide powder is passed through demagnetizer 1 to remove magnetic impurities before entering the silo and then being packaged as a finished product. In addition, before the nano-titanium dioxide powder leaves the silo and is packaged as a finished product, it can also pass through demagnetizer 1 again to remove magnetic impurities, which can further reduce magnetic impurities.
[0073] Specifically, in some implementation methods, such as Figures 4 to 8 As shown, the demagnetizer 1 includes a delivery tube 11, a contact tube 12, and a magnetic rod 13.
[0074] The conveying pipe 11 has a conveying channel; the conveying pipe 11 is connected to the deacidification device 8. The contact pipe 12 is sealed through the body of the conveying pipe 11, that is, the contact pipe 12 and the conveying pipe 11 are in sealed contact, effectively preventing powder leakage from the connection. The contact pipe 12 is arranged along the intersecting direction of the conveying channel. It should be noted that the conveying direction of the conveying channel is the direction of material flow inside the pipe, which is also the direction of the main axis of the conveying pipe 11. The axis of the contact pipe 12 is neither parallel nor coincident with the axis of the conveying pipe 11. The two axes form an angle greater than 0 degrees and less than 180 degrees in space. Specifically, in this embodiment, the axis of the contact pipe 12 is perpendicular to the axis of the conveying pipe 11, that is, the contact pipe 12 is transversely inserted through the body of the conveying pipe 11. The contact pipe 12 has a magnetically permeable structure. At least one end of the contact tube 12 is an open end, and the magnetic rod 13 is movably disposed inside the contact tube 12 and can be pulled away from the contact tube 12 along the open end.
[0075] Understandably, when the demagnetizer 1 is used for demagnetizing gas-phase nano titanium dioxide powder (hereinafter referred to as nano titanium dioxide), the input end and output end of the conveying pipe 11 can be connected to the deacidification device 8 and the silo in the nano titanium dioxide preparation device, respectively. After deacidification, the nano titanium dioxide is passed into the conveying pipe 11, magnetic impurities are removed, and then it enters the silo and is packaged as a finished product.
[0076] Specifically, the conveying pipe 11 has an input end and an output end communicating with the conveying channel. Both the input end and the output end are provided with flange connectors 14. The conveying pipe 11 is sealed and connected to the deacidification device 8 and the silo respectively through the flange connectors 14 at both ends. The deacidified nano-titanium dioxide directly enters the conveying pipe 11 for demagnetization impurity treatment. A contact pipe 12 is provided through the conveying pipe 11, penetrating the pipe body of the conveying pipe 11, and at least one end of the contact pipe 12 is an open end, so that the magnetic rod 13 can be inserted into the contact pipe from the open end. Alternatively, the magnetic rod 13 can be pulled out from the contact tube 12. Therefore, when it is necessary to remove magnetic impurities from the deacidified nano-titanium dioxide, the magnetic rod 13 is inserted into the contact tube 12. Since the contact tube 12 is a magnetically permeable structure, the magnetic rod 13 can penetrate the contact tube 12 through magnetic force to attract and fix magnetic foreign objects on the surface of the contact tube 12, thereby adsorbing the magnetic impurities in the nano-titanium dioxide flowing through the conveying channel, thus effectively removing the magnetic impurities in the nano-titanium dioxide, and the magnetic impurities do not directly contact the magnetic rod 13. After the nano-titanium dioxide is demagnetized, when the outer surface of the contact tube 12 has magnetic impurities adsorbed and needs to be cleaned, the magnetic rod 13 is pulled out from the contact tube 12, the magnetism of the contact tube 12 disappears, and then compressed air is introduced into the conveying tube 11 for purging, which can remove the magnetic impurities inside the conveying tube 11 and the outer surface of the contact tube 12. Therefore, the internal structure can be cleaned without disassembling the demagnetizer 1, and the operation is simple and convenient.
[0077] In some embodiments, the contact tube 12 is made of titanium, which facilitates magnetic penetration and is corrosion-resistant, effectively preventing powder corrosion of the titanium material. It should be noted that the wall thickness of the contact tube 12 and the size of the magnetic rod 13 can be specifically set according to the required magnetic force, and no particular limitations are imposed here. Furthermore, the contact tube 12 can also be made of a soft magnetic material, which refers to magnetic materials with low coercivity and high permeability, such as iron-silicon alloys, soft magnetic ferrites, metallic glasses, and amorphous nanocrystalline alloys, etc., and no particular limitations are imposed here.
[0078] In some implementations, such as Figure 5As shown, the open end of the contact tube 12 is provided with a movably closing sealing cap 121, and the sealing cap 121 is provided with an air inlet 122 communicating with the internal space of the contact tube 12. The contact tube 12 is provided with a blow hole 123 on the tube body inside the conveying tube 11. There is a cavity between the outer wall of the magnetic rod 13 and the inner wall of the contact tube. The air inlet 122, the cavity and the blow hole 123 are connected in sequence to form a blow channel. It should be noted that the air inlet 122 can be connected to an external gas generator. By controlling the opening and closing of the air inlet 122, specifically through a gas valve, gas, such as filtered air, can be introduced into the conveying pipe 11 during the demagnetization of nano-titanium dioxide inside the conveying pipe 11 through the spray channel formed by the air inlet 122, the cavity, and the spray hole 123 connected in sequence. On the one hand, it can blow away the nano-titanium dioxide adsorbed on the surface of the contact tube 12 due to electrostatics, and on the other hand, it can disperse the nano-titanium dioxide agglomerates, exposing the magnetic impurities wrapped in the agglomerates and adsorbing them onto the surface of the contact tube 12. This also improves the fluidity of the nano-titanium dioxide powder, thereby effectively improving the adsorption of magnetic particles in the agglomerates, especially the adsorption efficiency of tiny magnetic particles, and thus improving the demagnetization effect.
[0079] In some embodiments, the magnetic rod 13 includes a magnetic rod body and a protective sleeve. The protective sleeve is fitted onto the magnetic rod body and has a magnetically permeable structure. Since the contact tube 12 has a blowhole 123, during air blowing, a small amount of magnetic impurities may fall through the blowhole 123 into the interior of the contact tube 12 and adhere to the surface of the magnetic rod 13. In this embodiment, by setting the sleeve structure of the protective sleeve and the magnetic rod body, the protective sleeve can wrap around the magnetic rod body. This effectively prevents magnetic impurities from directly adsorbing onto the surface of the magnetic rod body. Furthermore, during cleaning, removing the magnetic rod body from the protective sleeve causes the sleeve to lose its magnetism. Shaking the protective sleeve removes the magnetic impurities adhering to its surface. The protective sleeve, also a magnetically permeable structure, combined with the contact tube 12, effectively prevents the magnetic properties of the magnetic rod body from disappearing after being separated by the protective sleeve and contact tube 12, thus avoiding affecting the adsorption effect of magnetic impurities. Specifically, in this embodiment, the protective sleeve is a polytetrafluoroethylene (PTFE) tube, and the magnetic field lines of the magnetic rod body pass through it with almost no attenuation or deflection. Alternatively, the protective sleeve can also be made of a soft magnetic material, which refers to magnetic materials with low coercivity and high permeability, such as iron-silicon alloys, soft magnetic ferrites, metallic glasses, and amorphous nanocrystalline alloys, etc., without particular limitation.
[0080] In some implementations, such as Figure 7As shown, the axial line of the blow hole 123 is inclined relative to the radial line of the contact tube 12, and the blow hole 123 extends along the circumferential direction of the contact tube 12 to form an arc-shaped hole structure in the tube body of the contact tube 12. Understandably, when high-pressure gas is ejected through this specially configured blow hole 123, its flow path is simultaneously guided by the arc-shaped inclined surface and the tilt angle of the blow hole 123. This results in the airflow not being ejected in a straight line, but rather forming a spiral airflow tightly adhering to the wall of the contact tube 12. This improves the flow path and the purging effect. Furthermore, when this spiral airflow impacts the powder, it causes the powder to tumble and disperse in the swirling flow, applying multi-directional shear force to effectively disperse the nano-titanium dioxide agglomerates. The spiral path also effectively reduces the occurrence of nano-titanium dioxide falling from the conveying tube 11 into the contact tube 12, thus reducing the loss of nano-titanium dioxide. Preferably, in the radial projection direction of the contact tube 12, the angle between the line connecting the air inlet and outlet of the blowhole 123 and the radial direction of the contact tube 12 is 70°~80°, more preferably 74°~76°; in the axial projection direction of the contact tube 12, the angle between the line connecting the air inlet and outlet of the blowhole 123 and the axial direction of the contact tube 12 is 25°~35°, more preferably 28°~32°. This specific angle setting allows the airflow ejected from the blowhole 123 to smoothly form a stable spiral airflow, providing a better purging effect.
[0081] In some implementations, such as Figure 6 As shown, multiple spray holes 123 are provided. The multiple spray holes 123 are spaced apart and staggered, and form a diamond arrangement structure at opposite ends of the contact tube 12. This allows the spiral airflow ejected from the spray holes 123 to meet, intertwine and superimpose in the conveying tube 11, thereby forming a three-dimensional turbulent airflow, which further increases the probability of collision with nano-titanium dioxide and effectively disperses the nano-titanium dioxide agglomerates.
[0082] In some embodiments, the air outlet of the blow hole 123 is oriented toward the input end of the conveying pipe 11, so that the incoming nano-titanium dioxide is opposed to the airflow ejected from the blow hole 123, thereby further improving the dispersibility of the powder.
[0083] In some implementations, such as Figure 4 As shown, multiple contact tubes 12 and magnetic rods 13 are provided, with each contact tube 12 corresponding to one of the magnetic rods 13, and the distance between two adjacent contact tubes 12 is 10mm to 50mm. The contact tubes 12 can be arranged in parallel or in a crisscross pattern, maintaining a distance of 10mm to 50mm between each contact tube. This arrangement effectively adsorbs magnetic impurities in the nano-titanium dioxide while allowing the nano-titanium dioxide to pass through smoothly.
[0084] In some embodiments, multiple demagnetizers 1 are provided, connected in parallel, and each demagnetizer 1 has a control valve at its input end; each demagnetizer 1 is connected to the deacidification device 8. Understandably, by designing parallel dual demagnetizer channels 1 and controlling their opening and closing with independent control valves, operational flexibility, production continuity, and ease of maintenance in the iron removal process can be achieved. Specifically, when the surface of the contact tube 12 of one demagnetizer 1 needs cleaning due to adsorption of magnetic impurities, the operator only needs to close the control valve of that demagnetizer 1 to safely remove the magnetic rod 13 and use compressed air to blow away the impurities accumulated on the surface and tube wall of the magnetic rod 13. Simultaneously, the other parallel demagnetizer 1 can remain independently open to continue adsorbing magnetic substances from the introduced nano-titanium dioxide, thus ensuring uninterrupted production and achieving continuous production and impurity removal. Alternatively, two demagnetizers 1 can be opened simultaneously to effectively improve the impurity removal effect.
[0085] The present invention will be described below with reference to specific embodiments.
[0086] Example 1
[0087] The nanopowder preparation device used in this embodiment is as follows: Figures 1 to 8 As shown.
[0088] The preparation method of this nano-titanium dioxide includes the following steps:
[0089] (1) The raw material TiCl4 liquid passes through the first filter at a flow rate of 25 kg / h, and is then vaporized in a vaporizer and output to the reactor at a flow rate of 15 kg / h. The reaction hydrogen and reaction air, which are filtered by a three-stage gas filter, enter the reactor at flow rates of 0.43 kg / h and 48 kg / h, respectively. After being mixed evenly with the vaporized TiCl4, they are ignited and reacted in the reactor. The gas-solid mixture after the reaction enters the aggregator, and the temperature of the aggregator is controlled at 280°C to obtain aggregates. The aggregates are then passed into a cyclone separator for separation. The solid reaction products separated by the cyclone separator are sequentially fed into a four-stage deacidification furnace. The deacidification auxiliary gas passes through a three-stage gas filter, is mixed with vaporized pure water, and is heated by an electromagnetic heater at a flow rate of 50 kg / h, a water vapor flow rate of 5 kg / h, and a gas temperature of 550°C. The gas reacts with the solid powder in the deacidification furnace to remove the acid and obtain nano-titanium dioxide. After deacidification, the nano-titanium dioxide was demagnetized by a demagnetizer to obtain demagnetized nano-titanium dioxide (sample 1).
[0090] Example 2
[0091] The preparation method of nano-titanium dioxide in this embodiment differs from that in Example 1 in that the deacidification gas temperature is 650°C. All other steps are the same as in Example 1.
[0092] Sample #2 was obtained.
[0093] Example 3
[0094] The difference between the preparation method of nano-titanium dioxide in this embodiment and that in Example 1 is that the deacidification gas temperature is 450°C. The other steps are the same as in Example 1.
[0095] Sample #3 was obtained.
[0096] Example 4
[0097] The preparation method of nano-titanium dioxide in this embodiment differs from that in Example 1 in that TiCl4, the reaction gas, and the deacidification auxiliary gas were not filtered. The other steps are the same as in Example 1.
[0098] Sample #4 was obtained.
[0099] Example 5
[0100] The preparation method of nano-titanium dioxide in this embodiment differs from that in Example 1 in that the TiCl4 was not filtered. All other steps are the same as in Example 1.
[0101] Sample #5 was obtained.
[0102] Example 6
[0103] The difference between the preparation method of nano-titanium dioxide in this embodiment and that in Example 1 is that the deacidified nano-titanium dioxide was not demagnetized. The other steps are the same as in Example 1.
[0104] Sample #6 was obtained.
[0105] Example 7
[0106] The difference between the preparation method of nano-titanium dioxide in this embodiment and that in Embodiment 1 is that the deacidification furnace uses an internal quartz heating tube, employs internal heating, sets the deacidification temperature to 450°C, and sets the deacidification auxiliary gas temperature to 150°C. Other steps are the same as in Embodiment 1.
[0107] Sample #7 was obtained.
[0108] Example 8
[0109] The difference between the preparation method of nano-titanium dioxide in this embodiment and that in Example 1 is that the deacidification furnace uses an internal quartz heating tube, employs internal heating, sets the deacidification temperature to 380°C, and sets the deacidification auxiliary gas temperature to 150°C. Other steps are the same as in Example 1.
[0110] Sample #8 was obtained.
[0111] The crystal form and proportion of the samples obtained in the above embodiments and comparative examples were determined by XRD.
[0112] The deacidification effect was characterized by testing the pH value of a 4% suspension.
[0113] Its chlorine removal effect was characterized by chloride content testing.
[0114] The content of metal impurities in the sample was tested by ICP-OES.
[0115] The content of magnetic foreign matter in a sample is tested by magnetic foreign matter testing.
[0116] The cleanliness tester was used to test the metal particle impurities in the sample (particles with a diameter of 25-100 μm were counted).
[0117] The content of large particles in the sample was determined by the residue content on a 45μm sieve.
[0118] The test results are shown in Table 1.
[0119] Table 1 Test results of basic indicators of the samples
[0120]
[0121]
[0122] The results from samples 1#-3# and 4#-8# show that by increasing the filtration of reaction raw materials and reaction gases, combining the demagnetization treatment of the deacidified products, and controlling the temperature of the deacidification auxiliary gas for heating deacidification, the proportion of anatase crystals in the prepared nano-titanium dioxide can be higher than 80%, and the contents of chlorine, iron, sodium, calcium, copper, zinc, cadmium, chromium, lead, and magnetic foreign matter are significantly reduced.
[0123] The results from samples 1#-3# show that, under otherwise unchanged conditions, increasing the temperature of the deacidification auxiliary gas reduces the chloride content but decreases the proportion of anatase crystals, thus affecting the catalytic performance of the powder.
[0124] The results from samples #1, #4, and #5 show that the reaction raw material TiCl4 and the reaction gas were all filtered. Compared to samples where the reaction raw material TiCl4, the reaction gas, and the deacidification auxiliary gas were not filtered, or the raw material TiCl4 was not filtered, the content of metallic impurities such as sodium, calcium, copper, and zinc was significantly reduced, and the amount of magnetic foreign matter was also reduced.
[0125] The results from samples #1 and #6 show that adding a demagnetizer to the deacidified product significantly reduces the content of magnetic foreign matter compared to deacidified nano-titanium dioxide without demagnetization, and also reduces the content of some metal impurities.
[0126] The results from samples 1# and 7#-8# show that although the internal heating method of the deacidification furnace improves the deacidification efficiency and the pH value of the product, it cannot effectively reduce the chloride content. Instead, it is prone to causing local overheating, which can lead to sintering of the product and an increase in large particles (increased sieve residue content).
[0127] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0128] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing high-purity nano-titanium dioxide, characterized in that, Includes the following steps: The reactant TiCl4 and the reactant gas were filtered separately and then mixed in the reactor. The resulting mixture is ignited and then fed into a reactor for combustion to produce reaction products. The resulting reaction product is fed into a deacidification device, and a deacidification auxiliary gas, which has been heated and filtered by an electromagnetic heater, is also fed into the deacidification device. The deacidification auxiliary gas and the reaction product are mutually counteracted in the deacidification device to deacidify the product and obtain nano-titanium dioxide. The temperature of the deacidification auxiliary gas is 450℃~600℃. The obtained nano-titanium dioxide is demagnetized by passing it through a demagnetizer, thus obtaining the high-purity nano-titanium dioxide. The demagnetizer includes a delivery tube, a contact tube, and a magnetic rod; The conveying pipe has a conveying channel inside, and the conveying pipe is connected to the deacidification device; The contact tube passes through the body of the conveying tube and is arranged along the intersecting direction of the conveying channel; the contact tube is a magnetically penetrable structure; at least one end of the contact tube is an open end, and the magnetic rod is movably disposed inside the contact tube and can be pulled away from the contact tube along the open end; The open end of the contact tube is provided with a movably closing sealing cap, and the sealing cap is provided with an air inlet that communicates with the internal space of the contact tube. The contact tube located inside the conveying tube body is provided with a blow hole. There is a cavity between the outer wall of the magnetic rod and the inner wall of the contact tube. The air inlet, the cavity and the blow hole are connected in sequence to form a blow channel. The axial line of the blow hole is inclined relative to the radial line of the contact tube, and the blow hole extends along the circumferential direction of the contact tube to form an arc-shaped inclined hole structure in the tube body of the contact tube.
2. The preparation method according to claim 1, characterized in that, The TiCl4 in the reaction raw materials is liquid. The TiCl4 liquid is filtered through a first filter and then vaporized and introduced into the reactor. The first filter is equipped with a first filter element. The TiCl4 liquid enters from the bottom of the first filter, flows through the first filter element, and then flows out from the top of the first filter.
3. The preparation method according to claim 2, characterized in that, The first filter element is made of porous polytetrafluoroethylene with a pore size of 0.005μm~0.1μm; And / or, the first filter element is provided in multiple parts, each of the first filter elements is tightly fitted together, and the outer wall of the outermost first filter element is in close contact with the inner wall of the first filter.
4. The preparation method according to claim 3, characterized in that, The pore size of the first filter element is 0.008μm~0.05μm.
5. The preparation method according to claim 1, characterized in that, The reaction gas includes hydrogen and combustion-supporting gas; the hydrogen and combustion-supporting gas are filtered through a second filter before being introduced into the reactor. The second filter includes a gas filter, and multiple gas filters are connected in series to form a multi-stage filtration structure; each gas filter is provided with a second filter element, the pore size of the second filter element is 0.005μm~1μm, and the pore size of the second filter element in the gas filter from the first stage to the last stage decreases sequentially.
6. The preparation method according to claim 5, characterized in that, The second filter comprises three gas filters connected in series; the second filter element in the first-stage gas filter has a pore size of 0.3μm to 0.7μm, the second filter element in the second-stage gas filter has a pore size of 0.08μm to 0.2μm, and the second filter element in the third-stage gas filter has a pore size of 0.008μm to 0.05μm.
7. The preparation method according to claim 5 or 6, characterized in that, The deacidification auxiliary gas is air or nitrogen; And / or, the deacidification auxiliary gas is mixed with vaporized pure water, heated by an electromagnetic heater, filtered through another second filter, and then enters the deacidification device from the bottom to counteract the reaction products input from the top of the deacidification device for deacidification.
8. The preparation method according to claim 1, characterized in that, The magnetic rod includes a magnetic rod body and a protective sleeve. The protective sleeve is fitted onto the magnetic rod body and has a magnetically permeable structure. And / or, the conveying pipe body has an input end and an output end communicating with the conveying channel, and both the input end and the output end are provided with flange connectors; And / or, multiple contact tubes and magnetic rods are provided, with each contact tube and magnetic rod corresponding to the other, and the distance between two adjacent contact tubes is 10mm to 50mm.
9. The preparation method according to any one of claims 1-6, characterized in that, The deacidification device includes multiple deacidification furnaces connected in series to form a multi-stage deacidification structure; And / or, after the resulting mixture is ignited and enters the reactor for combustion reaction, and before the resulting reaction product is input into the deacidification unit, the following steps are also included: The obtained reaction product is passed into an aggregator to aggregate the solid product to obtain an aggregate, and the obtained aggregate is passed into a cyclone separator to separate the solid reaction product. And / or, the temperature inside the reactor is 280℃~400℃; And / or, the temperature of the deacidification auxiliary gas is 500℃~580℃.
10. The preparation method according to claim 9, characterized in that, The temperature of the deacidification auxiliary gas is 540℃~560℃.
Citation Information
Patent Citations
Synthesis method of nano titanium dioxide
CN113353978A